Fig. 1 in Helminths Of Antarctic Rockcod Notothenia Coriiceps (Perciformes, Nototheniidae) From The Akademik Vernadsky Station Area (Argentine Islands, West Antarctica): New Data On The Parasite Community - Kuzmina, T. A.; Salganskij, O. O.; Lisitsyna, O. I.; Korol, E. M. (Zenodo, 2020)
Fig. 1. Prevalence (in %) and mean intensity of helminth species found in Notothenia coriiceps in the waters surrounding the Ukrainian Antarctic station "Akademik Vernadsky" in 2014–2015. Published as part of Kuzmina, T. A., Salganskij, O. O., Lisitsyna, O. I. & Korol, E. M., 2020, Helminths Of Antarctic Rockcod Notothenia Coriiceps (Perciformes, Nototheniidae) From The Akademik Vernadsky Station Area (Argentine Islands, West Antarctica): New Data On The Parasite Community, pp. 99-110 in Zoodiversity 54 (2) on page 105, DOI:10.15407/zoo2020.02.099, http://zenodo.org/record/6455500